The Next Smart Move : Towards Smart Surfaces and Sensors - Bhattacharjee, Sandeep (Indian Journal of Computer Science, 2020)
In this research paper we have tried to understand the different factors that are leading to development of smart surfaces and smart sensors that could revolutionize the way machines communicate and respond to the environment. The ultra convergence of machines with inbuilt high capacity sensors and intelligent surfaces equipped with software algorithms can transform the way we know and use machines. This research paper is an effort to identify the paradigms and facts associated with such development. The observation and summarization of facts can thus lead to better understanding of the concept of smart surfaces and sensors. Some of the major findings were smart surface applications in automobiles, urban planning, health monitoring devices, pollution control mechanisms, temperature control systems, and disaster alert systems were found to be related to smart sensors. This information can be of immense help for academicians, researchers, students, and scholars who may be interested in this domain of knowledge.